Circulating tsRNAs serve as potential biomarkers for predicting postoperative delirium in elderly patients receiving lower extremity orthopedic surgery - Cao, Angyang; Zhao, Rui; Chen, Chunqu; Wu, Can; Zhang, Yiwei; Huang, Changshun; Zhu, Binbin (Frontiers in Psychiatry, 2025)
BackgroundPostoperative delirium (POD) is a serious neuropsychiatric complication in elderly surgical patients, yet its pathogenesis remains incompletely understood. Transfer RNA-derived small RNAs (tsRNAs) have emerged as crucial regulators in neurological disorders. We investigated whether specific tsRNAs could serve as predictive biomarkers for POD.MethodsThis study conducted a prospective case-control study of 158 elderly patients (≥60 years) undergoing orthopedic surgery. Plasma samples were collected preoperatively and on postoperative day 3.tsRNA expression profiles were analyzed using RNA sequencing and validated by RT-qPCR. Propensity score matching was performed to balance demographic and clinical variables. The predictive value of candidate tsRNAs was assessed using ROC analysis, and their potential functions were explored through bioinformatic analyses.ResultsAmong 128 non-POD and 30 POD patients, two tsRNAs (Other-14: 31-tRNA-Gly-CCC-3 and Other-39: 73-tRNA-Arg-TCG-5) showed significantly elevated preoperative levels in POD patients (p<0.001).ROC analysis revealed strong predictive performance (AUC=0.868 and 0.956, respectively).These differences persisted in the propensity-matched cohort (29 pairs).Bioinformatic analyses indicated enrichment in pathways related to neurotransmission, inflammation, and metabolism.ConclusionThis study identified novel tsRNA biomarkers that robustly predict POD risk and provide insights into its molecular pathogenesis. These findings may facilitate early risk stratification and preventive interventions.